2008
DOI: 10.2495/wm080611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an organic residue on herbicide field dissipation

Abstract: The aim of this work was to study the effect of the application of a solid waste from olive oil production (alperujo) on the movement and persistence of the herbicide diuron [3-(3,4-dichlorophenyl)-1,1-dimethylurea]. The application of alperujo, fresh or composted, to the land has been shown to be an extremely effective contribution to increasing crop yields and to maintaining or improving soil fertility. An experimental olive grove located in Mengibar (Jaen, Spain) was divided into two plots: 1. Plot without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated the beneficial effects of TPOMW in restoring crop productivity in degraded soils (López-Piñeiro et al, 2006, but very few studies have investigated diuron's behaviour in fresh TPOMW-amended soils Cox et al, 2007), and even fewer have been carried out in situ under field conditions, due to the high cost and difficulty (Cabrera et al, 2008a(Cabrera et al, ,b, 2009). In addition, to the best of our knowledge, there is no information on the influence of TPOMW organic matter transformation on diuron's fate in soils following repeated applications of this waste also under field conditions, although such information would be useful from the environmental perspective of the management of this herbicide in soils receiving this waste.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have demonstrated the beneficial effects of TPOMW in restoring crop productivity in degraded soils (López-Piñeiro et al, 2006, but very few studies have investigated diuron's behaviour in fresh TPOMW-amended soils Cox et al, 2007), and even fewer have been carried out in situ under field conditions, due to the high cost and difficulty (Cabrera et al, 2008a(Cabrera et al, ,b, 2009). In addition, to the best of our knowledge, there is no information on the influence of TPOMW organic matter transformation on diuron's fate in soils following repeated applications of this waste also under field conditions, although such information would be useful from the environmental perspective of the management of this herbicide in soils receiving this waste.…”
Section: Introductionmentioning
confidence: 98%